Public relations role of government-linked companies in green purchase behaviour: a case study on Felda Global Ventures Holding Berhad and Petroliam Nasional Berhad - Wahid, Azizah; Ahmad, Jamilah (academy IRMBR, 2015)
In this modern era of public relations field, green is a fundamental guideline to promote strategies and practices. Government promotes strategies to boost more environmentally sustainable consumption patterns. It is necessary for the public relations practitioners to communicate effectively in order to influence green purchase behaviour among public. The purpose of this research is to examine the role of public relations in Government-linked Companies (GLCs) in communicating information on its green initiatives and strategies towards influencing green purchase. This paper also investigates the practitioners’ perceptions on green products and the level of understanding on green purchase behaviour factors. Data were collected from ten public relations practitioners from Petroliam Nasional Berhad and Felda Global Ventures through in depth interviews on their roles in promoting green purchase behaviour. The results obtained indicate that the public relations practices of both companies have partially fulfilled the Excellence Theory Principles, which integrate the practices of communication technician and communication facilitator as their public relations roles. Thus, this study concludes that the public relations practitioners’ roles in GLCs are not effective enough to influence green purchase behaviour towards public